STRATEGI PENGEMBANGAN EKOWISATA BERBASIS PENYU HIJAU DI KAWASAN PANTAI SUKAMADE TAMAN NASIONAL MERU BETIRI - Dylla Axaraliefya; Nina Herlina; Toto Supartono (Journal of Forestry And Environment, 2023)
The Sukamade Beach area of Meru Betiri National Park is one of the distribution areas for green turtles in Indonesia. The existence of these green turtles has the potential to become an ecotourism attraction. The aim of this research is to determine the potential of green turtles (nesting season and nesting behavior) and to develop green turtle-based ecotourism for Meru Betiri National Park Management. The research method used for data collection is the "simple random sampling" method. Data collection includes data on green turtle potential (nesting season and nesting behavior) and green turtle-based ecotourism development strategies. The research data shows that the potential for green turtle-based ecotourism is data on the number of green turtles that appear on the surface of Sukamade Beach, the number of green turtle eggs, the number of green turtle eggs that hatch into hatchlings, the number of green turtle hatchlings that are released into the sea, the number of green turtles laying eggs and the behavior of green turtles when laying eggs, while the green turtle-based ecotourism development strategy that is appropriate for ecotourism development is the strength-opportunity (S-O) strategy by creating a strategy that uses strengths to take advantage of opportunities in the form of increasing ecotourism objects with the "Green Turtle Enchantment" program for the purposes of education and research. The suggestions in this research are the need to monitor vegetation and the distribution of green turtle nests so that the existence of green turtles will remain sustainable, create an interpretation board regarding information on the existence, benefits and behavior of green turtles, collaborate with the community and village government in management around the Sukamade Beach area so that it does not cause problems. Social reflection and further research on Habitat Specifications for Green Turtles Laying Eggs on Sukamade Beach, Meru Betiri National Park to make it easier for managers to find out the location of green turtles nesting.Kawasan Pantai Sukamade Taman Nasional Meru Betiri merupakan salah satudaerah penyebaran penyu hijau di Indonesia. Keberadaan penyu hijau tersebut sangatberpotensi untuk dijadikan sebagai salah satu objek ekowisata. Tujuan penelitian iniadalah mengetahui potensi penyu hijau (musim bertelur dan perilaku bertelur) danmenyusun engembangan ekowisata berbasis penyu hijau kepada Pengelola Taman Nasional Meru Betiri. Metode penelitian yang digunakan untuk pengumpulan data yaitumenggunakan metode “simple random sampling”. Pengumpulan data meliputi data potensi penyu hijau (musim bertelur dan perilaku bertelur) dan strategi pengembangan ekowisata berbasis penyu hijau. Data hasil penelitian menunjukkan bahwa potensi ekowisata berbasis penyu hijau adalah data jumlah keberadaan penyu hijau yang muncul di permukaan Pantai Sukamade, jumlah telur penyu hijau, jumlah telur penyu hijau yang menetas menjadi tukik, jumlah tukik penyu hijau yang di lepas ke laut, jumlah penyu hijau yang bertelur dan perilaku penyu hijau saat bertelur sedangkan strategi pengembangan ekowisata berbasis penyu hijau yang tepat untuk pengembangan ekowisata yaitu strategi kekuatan-peluang (S-O) dengan menciptakan strategi yang menggunakan kekuatan untuk memanfaatkan peluang berupa peningkatan objek ekowisata dengan program “Pesona Penyu Hijau” untuk keperluan pendidikan dan penelitian. Saran dalam penelitian ini adalah perlunya monitoring vegetasi dan penyebaran sarang penyu hijau sehingga keberadaan penyu hijau akan tetap lestari, pembuatan papan interpretasi mengenai informasi keberadaan, manfaat dan perilaku penyu hijau, kerjasama dengan masyarakat dan pemerintah desa dalam pengelolaan di sekitar Kawasan Pantai Sukamade sehingga tidak menimbulkan kecemburuan sosial dan penelitian lanjutan tentang Spesifikasi Habitat Penyu Hijau Bertelur di Pantai Sukamade Taman Nasional Meru Betiri agar dapat mempermudah pengelola untuk mengetahui lokasi peneluran penyu hijau